Predictive Accuracy of Quick Sequential Organ Failure Assessment for Hospital Mortality Decreases With Increasing Comorbidity Burden Among Patients Admitted for Suspected Infection*. Issue 8 (August 2019) - Parks Taylor, Stephanie; McWilliams, Andrew; Taylor, Brice T.; Heffner, Alan C.; Chou, Shih-Hsiung; Runyon, Michael; Cunningham, Kyle; Evans, Susan L.; Gibbs, Michael; Russo, Mark; Rossman, Whitney; Murphy, Stephanie E.; et al.
Abstract : Objectives: Evaluate the accuracy of the quick Sequential Organ Failure Assessment tool to predict mortality across increasing levels of comorbidity burden. Design: Retrospective observational cohort study. Setting: Twelve acute care hospitals in the Southeastern United States. Patients: A total of 52, 187 patients with suspected infection presenting to the Emergency Department between January 2014 and September 2017. Interventions: None. Measurements and Main Results: The primary outcome was hospital mortality. We used electronic health record data to calculate quick Sequential Organ Failure Assessment risk scores from vital signs and laboratory values documented during the first 24 hours. We calculated Charlson Comorbidity Index scores to quantify comorbidity burden. We constructed logistic regression models to evaluate differences in the performance of quick Sequential Organ Failure Assessment greater than or equal to 2 to predict hospital mortality in patients with no documented (Charlson Comorbidity Index = 0), low (Charlson Comorbidity Index = 1–2), moderate (Charlson Comorbidity Index = 3–4), or high (Charlson Comorbidity Index ≥ 5) comorbidity burden. Among the cohort, 2, 030 patients died in the hospital (4%). No comorbidities were documented for 5, 038 patients (10%), 9, 235 patients (18%) had low comorbidity burden, 12, 649 patients (24%) had moderate comorbidity burden, and 25, 265 patients (48%) had high comorbidity burden. Overall model discrimination for quick Sequential Organ Failure Assessment greater than or equal to 2 was the area under the receiver operating characteristic curve of 0.71 (95% CI, 0.69–0.72). A model including both quick Sequential Organ Failure Assessment and Charlson Comorbidity Index had improved discrimination compared with Charlson Comorbidity Index alone (area under the receiver operating characteristic curve, 0.77; 95% CI, 0.76–0.78 vs area under the curve, 0.61; 95% CI, 0.59–0.62). Discrimination was highest among patients with no documented comorbidities (quick Sequential Organ Failure Assessment area under the receiver operating characteristic curve, 0.84; 95% CI; 0.79–0.89) and lowest among high comorbidity patients (quick Sequential Organ Failure Assessment area under the receiver operating characteristic curve, 0.67; 95% CI, 0.65–0.68). The strength of association between quick Sequential Organ Failure Assessment and mortality ranged from 30.5-fold increased likelihood in patients with no comorbidities to 4.7-fold increased likelihood in patients with high comorbidity. Conclusions: The accuracy of quick Sequential Organ Failure Assessment to predict hospital mortality diminishes with increasing comorbidity burden. Patients with comorbidities may have baseline abnormalities in quick Sequential Organ Failure Assessment variables that reduce predictive accuracy. Additional research is needed to better understand quick Sequential Organ Failure Assessment performance across different comorbid conditions with modification that incorporates the context of changes to baseline variables. Abstract : Supplemental Digital Content is available in the text.